Asuhan Kebidanan Komprehensif Pada Ny. D Dengan Resiko Tinggi : (Studi Kasus Terhadap Ny D Di Puskesmas Pangkah Kabupaten Tegal Tahun 2023) - Islakhul Zachro; Istiqomah Dwi Andari; Riska Arsita (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
In 2022, Pangkah Public Health Center in Tegal Regency recorded 2 cases of maternal deaths, attributed to hemorrhage and umbilical cord embolism. Data obtained from the health center in 2023 revealed a total of 874 pregnant women, with 475 categorized as high-risk. Risk factors included maternal age <20 years (17 cases), maternal age >35 years (133 cases), interpregnancy interval <2 years (31 cases), nutritional problems (109 cases), anemia (50 cases), presence of more than 5 children (17 cases), and others (118 cases). Among high-risk pregnancies, women aged >35 years and those falling into the "others" category were the two most prevalent groups. The general objective of this case study is to gain insights and real-life experiences in providing comprehensive midwifery care to Mrs. D at Pangkah Public Health Center in 2023, focusing on high-risk grandemultipara and women aged >35 years, utilizing the 7-step Varney midwifery care management and SOAP development data. This research adopts a case study approach, with Mrs. D, a 36-year-old grandemultipara with advanced maternal age, as the subject. Comprehensive care is provided throughout the antenatal, intrapartum, postpartum, and neonatal periods, including the application of Postnatal Massage therapy. From the data collected, it is concluded that the subject experienced numbness in her hands upon waking up from 38 weeks of gestation onwards. The patient perceives her pregnancy as highly risky due to being a grandemultipara and advanced maternal age, necessitating close monitoring by healthcare providers.